2020
DOI: 10.15672/hujms.518154
|View full text |Cite
|
Sign up to set email alerts
|

Radii of starlikeness and convexity of generalized Struve functions

Abstract: The main purpose of this paper is to determine the radii of starlikeness and convexity of the generalized k−Bessel functions for three different kinds of normalization by using their Hadamard factorization in such a way that the resulting functions are analytic in the unit disk of the complex plane. The characterization of entire functions from Laguerre-Pólya class plays an crucial role in this paper. Moreover, the interlacing properties of the zeros of k−Bessel function and its derivative is also useful in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this section, we are going to discuss some properties like monotonicity and log-concavity of the generalized Struve function by using its product representation which is known as Hadamard product or Weierstrassian decomposition. The generalized Struve function has the following series representation (see [12]):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we are going to discuss some properties like monotonicity and log-concavity of the generalized Struve function by using its product representation which is known as Hadamard product or Weierstrassian decomposition. The generalized Struve function has the following series representation (see [12]):…”
Section: Resultsmentioning
confidence: 99%
“…for q 2 N; p; b; c 2 C and > 0. The author studied some geometric properties such as starlikeness and convexity of generalized Struve function in [12]. Also, the author showed that the zeros of the generalized Struve function are all real.…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive information about the log-concavity and the log-convexity properties can be found in [13] and its references. In this study, motivated by the some earlier results which are given in [14,15], our main aim is to present some monotonic and log-concavity properties of generalized k-Bessel functions. Moreover, we give some specific examples regarding our obtained result by using the relationships between Bessel-type functions and elementary trigonometric and hyperbolic functions.…”
Section: Introductionmentioning
confidence: 99%
“…where J ν (x) and I ν (x) denote classical Bessel and modified Bessel functions of the first kind, respectively. In [15], the author studied some geomertric properties such as radii of starlikeness and convexity of generalized k-Bessel function. Also, the author gave an infinite product representation of generalized k-Bessel function by using Hadamard's theorem as follow (see [15, Lemma 1.1]):…”
Section: Introductionmentioning
confidence: 99%